ANALISIS KOMPREHENSIF PENUMBUHAN JIWA ENTREPRENEURSHIP SEBAGAI PENGUATAN EKONOMI MASYARAKAT (Studi Kasus Pada Masyarakat Sekarisidenan Surakarta) - Totok Susilo Pamuji Nugroho; Nina Adelina; Tities Wicaksono Pamuji Wibowo (Riset Manajemen dan Akuntansi, 2019)
This study aims to determine the entrepreneurial spirit constraints experienced by Indonesian society. The main objective in this research is many of graduates of leading state universities who participated in job search, even though they are expected to be able to create jobs. The method used in this study uses descriptive analysis method. Data collection by purposive sampling while testing the validity of the data using Person Product Moments. The dependent variable in this study is the level of education and capital while the independent variable is the entrepreneurial spirit as measured by five indicators (integrity, accuracy, calmness, risk estimation and confidence). The results of this study indicate that the level of education and capital does not affect significant with the entrepreneurial spirit. Thus this research refutes the existing paradigm where if highly educated and have large capital it will success with entrepreneurship.